MENINGKATKAN KEMAMPUAN PENJUMLAHAN MELALUI PENDEKATAN KETERAMPILAN PROSES BAGI ANAK TUNAGRAHITA RINGAN Di KELAS DASAR IV/C (Penelitian Tindakan Kelas Di SLB AL-Hidayah Maek) - Harmel - Harmel (Universitas Negeri Padang, 2012)
This research was done because there was light tungagrahita students at grade four who had difficulty in doing stackable sum down with saving technique. This problem happenend because the students found the difficulties in determining the place value when doing summation. In addition, the students were not able to determine how to put the result of summation and the aften forget to sum up the Tunagrahita students at basic class IV. The aim fo research is to improve stackable sum down ability with saving technique for light Tunagrahita students (KH and TN) at basic class IV SLB Al-Hidayah Maek. The tpe of the research is classroom action research the is conducted in from collaboration. At the first cycle that is conducted in four meetings, the students were taught about determining the palce value, putting the number based on the place value, putting the sum of saced number and doing exercise. The mean at the and of first cycle show that KH before students got the action was 50% and KH after getting the action is 80%. The students were able to do the exercise without teachers; help before getting the action and the students were able to do the exercises after getting the first action and they got 70%. At the second cycle that was done as long as four meetings, the stackable sum down with saving technique through the use of skill process approach shows that the studens’ ability improved. The result is KH at the first cycle were not able to do the exercise without teachers’ help and they got 80%. At the second cycle, they are able to do 5 exercise without teachers’ help and they got 50%. Besides, at the second cycle TN was able to do 5 exercise without teachers’ help and they got 50%. In addition, at the third cycle that is conductor in four meeting, the result shows that the students ability improve. KH was able to do 8 exercise without teachers; help and the students got 80% an TN was able to do 7 exercise and they got 70%. So, it suggested for the school, teachers and the next researchers to use skill process approach for improving summation ability for light Tunagrahita students.